PSYCHOLOGICAL FEATURES OF THE DEVELOPMENT OF THINKING IN PRESCHOOL CHILDREN (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The theories of thinking existing in modern psychology reflect various approaches to the study of thinking and reveal the essence, structure and features of the flow of mental activity in children of different ages in various processes of activity.